Utilization of Manufactured Sand with Partially Replacement of Natural Sand in Concrete - Pratik S Shata; Kartik A Patel (International Journal of Engineering and Management Research, 2023)
Natural Sand used in manufacturing concrete is sourced from natural river bed which if not replenished causes environmental concerns. Scarcity of good quality Natural River sand due to depletion of resources and restriction due to environmental consideration has made concrete manufactures to look for suitable alternative fine aggregate. This has prompted researchers to look for alternate material that could potentially replace natural river sand without adversely impacting properties of resulting concrete. A replacement of finer aggregates by a manufactured sand by varying proportions leads to the increase in both engineering & physical properties of concrete constituents which are to be considered in recent trends. In the present study manufactured sand with varying proportions from 0 to 60 % by its weight are mixed with concrete materials as a partial replacement with fine aggregates & analyzed for its physical and engineering properties, with the further analysis an introduction of manufactured sand in a proper proportion will lead to increase in the compressive strength by 15 to 20% for the concrete cubes which are being tested for 7 days, 14 days & 28 days strength.